(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Electric vehicles may significantly contribute to the global effort to prevent environmental issues by assisting in the reduction of emissions as well as reliance on fossil fuels. In-depth study has been done on Electric Vehicles (EV), which provide hope for lowering the greenhouse impact. In comparison to internal combustion engine vehicles, the plug-in hybrid electric vehicle (PHEV) offers a competitive vehicle performance as well as fuel efficiency thanks to advancements in generating electrics, energy storage, as well as support (ICEV). The advantages of electric cars considerably outweigh the expenses, as shown in the economical, societal, as well as environmental analyses parts of this site. Cost is the main barrier to the wide-scale adoption of electric-powered transportation, since gasoline and the cars that use it are more easily accessible, practical, and less expensive. The author discussed the how electric vehicle beneficial for the environment and how it helps to reduce greenhouse emission. This study focuses on the role and significance of electric vehicle and its benefits for our ecosystem. Findings of this study conclude that as such, people expect that via mass marketing as well as ecological education initiatives, people would feel energized and encouraged to drive an electric car.